Perlocutionary Speech Acts in Parenting Education Discourse on TikTok Social Media - Fitriyani, Hanifah; Prayitno, Harun Joko (Universitas Muhammadiyah Surakarta, 2023)
This research aims to describe the classification of perlocutionary speech acts in educational parenting discourse on the TikTok social media platform. The study utilizes a qualitative descriptive method, focusing on perlocutionary speech acts as the object of investigation. The subject of the research is the TikTok social media platform. Data and data sources for this study consist of sentences, expressions, or speech acts in educational parenting discourse on TikTok. Data collection techniques involve the free observation and note-taking method. Meanwhile, data analysis employs intralingual matching and pragmatic matching methods. The results of the research indicate that perlocutionary speech acts in educational parenting discourse on TikTok include: (1) directive perlocutionary speech acts of commands, totaling 4 data, (2) directive perlocutionary speech acts of requests, totaling 4 data, (3) directive perlocutionary speech acts of appeals, totaling 2 data, and (4) directive perlocutionary speech acts of giving advice, totaling 3 data.